Young Leaders for Indonesia Ananda Priantara dalam Perspektif Agensi Strukturasi - Wirayani, Kadek Cyntia; Nugroho, Wahyu Budi; Kamajaya, Gede; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This study aims to describe and analyze Young Leaders for Indonesia Ananda Priantara as a young leader through the perspective of Anthony Giddens' agency-structuration. The condition of the young generation who are referred to as prospective national leaders because of the demographic bonus currently facing Indonesia, thus achieving Golden Indonesia in 2045 amidst the flow of globalization that has a defectological impact in it. In carrying out these ideals, the role of a leader is needed who can encourage and motivate the young generation to find their interests and develop themselves so that they become leaders for this nation. The existence of Ananda Priantar with various experiences and awards that he has and his awareness of the role of leaders in empowering other young generations, creates an environment that can be a place to learn and develop that is beneficial for the young generation and society. Through the theory of structuration analysis, it describes how agency and structure are a unity that can recreate social structures and produce social change. The results of this study see how the figure of Ananda Priantar has an impact on society, especially the young generation.